Dryland climatology - Nicholson, Sharon E. (Cambridge University Press, 2011)
"A comprehensive review of dryland climates and their relationship to the physical environment, hydrology, and inhabitants. Chapters are divided into four major sections on background meteorology and climatology; the nature of dryland climates in relation to precipitation and hydrology; the climatology and climate dynamics of the major dryland regions on each continent; and an extensive review of long-term climate variability in the world's drylands. It includes key topics such as vegetation, geomorphology, desertification, micro-habitats, and adaptation to dryland environments. This interdisciplinary volume provides an extensive review of the primary literature (covering over 2500 references) and the conventional and satellite datasets that form key research tools for dryland climatology. Illustrated with over 100 photographs, it presents a unique view of dryland climates for a broad spectrum of researchers, environmental professionals and advanced students in climatology, meteorology, geography, environment science, earth system science, ecology, hydrology and geomorphology"--